Stakeholder perceptions of the WHO country offices in Africa: implications for organisational reforms - Olu, Olushayo Oluseun; Usman, Abdulmumini; Ba, Ndoungou Salla; Kabore, Patrick; Achu, Bei; Kakay, Mohammed; Kulausa, Hyelni; Rwamatwara, Egide; Okeibunor, Joseph; Chanda, Emmanuel; Gasasira, Alex; Cabore, Joseph (Frontiers in Public Health, 2025)
IntroductionEvidence from internal audits and other evaluation reports shows that the World Health Organisation Regional Office for Africa and its country offices have had varied relationships with their stakeholders, including governments, donors, non-governmental organsations, and the United Nations. As part of a wider organisational reform, a stakeholder perception study was conducted to understand the insights of the organisation’s stakeholders on the performance of its country offices.MethodsWe assessed stakeholders’ perceptions, expectations, and recommendations regarding the World Health Organisation African Region country offices using a self-administered questionnaire, conducted over multiple intervals from 2017 to 2020. Forty out of the forty-seven countries of the region were selected and included in the study. Respondents were purposively selected from the organisation’s key stakeholders in each country.ResultsResponses were received from 865 respondents from 40 countries, representing a 100% overall country response rate. Governmental institutions, UN agencies, NGOs/civil society, donors, and others constituted 35% (303), 25% (216), 22% (190), 11% (95), and 6% (52) of the respondents, respectively. Twenty-six percent (225) of the stakeholders considered the ability of the World Health Organisation African Region country offices to manage threats as fair or poor. They were unaware of the organisation’s core functions, particularly the function of shaping the research agenda and articulating evidence-based policy options. Regarding the accessibility/technology and timeliness of how the organisation communicates public health information, 38% (329) and 34% (294) of stakeholders, respectively, rated the organisation fairly and poorly. The majority of partners identified health system strengthening, communicable and non-communicable diseases prevention, emergency preparedness and response, immunisation, and polio eradication as the top five areas for the organisation to focus on at the country level. In general, many of the respondents would like to see improvements in the quality of the organisation’s technical assistance, better integration into the wider United Nations system, and better recognition of and support to civil societies. The donors (25%) were the most critical of the organisation.ConclusionWe recommend a comprehensive organisational reform programme to address the negative perceptions identified in this study and reinforce the positive findings.